The Effectiveness of Physical Exercise on the Speed and Endurance of Fencing Athletes: A Systematic Literature Review - Siahaan, Derry Renanda Putra; Rahmat, Alit; Damayanti, Nadia Fadilla; Ginanjar, Afan (Universitas Negeri Semarang, 2024)
Physical exercise is one of the essential aspects in maintaining health and physical fitness. This activity not only helps improve muscle strength and body endurance, but also plays a role in maintaining heart health, increasing flexibility, and reducing the risk of various chronic diseases such as diabetes and hypertension. In the modern era, where lifestyles tend to be more sedentary due to technological advancements and the prevalence of online work, it is crucial for every individual to remain physically active. This study aims to determine the effect of physical training on the performance of fencing athletes, with the main focus on speed, accuracy and endurance. This study uses the Systematic Literature Review (SLR) method, in which researchers collect data through accessible journal portals, especially Sinta, using the Harzing's Publish or Perish application. Out of 200 related articles, 6 were found to be relevant after a screening process using Covidence. The data analyzed in this study were drawn from the 2017–2024 period and are indexed in Sinta and publicly accessible. Based on the results and discussion, it can be concluded that regular and targeted physical training plays an important role in improving the performance of fencing athletes. Increasing explosive muscle strength results in athletes being able to make faster, more effective and targeted attacks on each stab accuracy, thus minimizing the opponent to make defensive movements.